1979
DOI: 10.2307/1953984
|View full text |Cite
|
Sign up to set email alerts
|

Social Amelioration through Mass Insurgency? A Reexamination of the Piven and Cloward Thesis

Abstract: Frances Fox Piven and Richard A. Cloward (1971, 1977) have argued that mass insurgency in the United States, occurring especially between 1964 and 1969, produced a series of responses by government, one of the most significant being massive expansion of welfare rolls. Using data on which they base their claim, this study examines the hypothesis that there is a positive association between social disorders and welfare caseload increases. The conclusion is that associations specified by Piven and Cloward are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Various researchers have provided empirical support for the relationship between civil disorder and welfare growth in the late 1960s (Betz, 1974;Jennings, 1979;Isaac and Kelly, 1981). Critics, however, have rejected this thesis upon finding no relationship between riottorn cities and increases in welfare (Durman, 1973;Albritton, 1979). Our analysis seeks to resolve these conflicting findings.…”
mentioning
confidence: 95%
“…Various researchers have provided empirical support for the relationship between civil disorder and welfare growth in the late 1960s (Betz, 1974;Jennings, 1979;Isaac and Kelly, 1981). Critics, however, have rejected this thesis upon finding no relationship between riottorn cities and increases in welfare (Durman, 1973;Albritton, 1979). Our analysis seeks to resolve these conflicting findings.…”
mentioning
confidence: 95%
“…Support for the social threat-welfare expansion thesis has been mixed. Some studies reported a direct, positive association between measures of intergroup threat (e.g., urban rioting) and the expansion of the AFDC program (Chamlin, 1992;Issac & Kelly, 1981;Jennings, 1983;Schram & Turbett, 1983), whereas others do not (Albritton, 1979;Betz, 1974;Durman, 1973). In an effort to make sense of those ambiguous findings, we attempted to take advantage of recent efforts to "end welfare as we know it" to evaluate Cloward's (1971, 1987) ideas concerning the relationship between the welfare contradiction and the enforcement of work norms.…”
Section: Discussionmentioning
confidence: 99%
“…The welfare state literature contains empirical evidence that supports Piven andCloward's (1971, 1993) thesis by demonstrating associations between civil disobedience and increases in social welfare policies in the latter half of the 1960 decade (Betz, 1974;Chamlin, 1992;Hicks & Swank, 1983;Isaac & Kelly, 1981;Jennings, 1979;Schram & Turbett, 1983a). Other researchers, however, inflicted a major blow to Piven and Cloward's (1971) Social Control Thesis upon finding no relationships between political unrest and growth in welfare expenditures in the late 1960s (Albritton, 1979;Durman, 1973). One explanation to these contradictory findings from Albritton (1979) and Durman (1973) was provided by Schram and Turbett (1983b):…”
Section: Theses Of Welfare Expansionmentioning
confidence: 99%